Research Status, Hot Spots and Trends of International Talent Cultivation: A CiteSpace-based Visualization Analysis - Feiping, Ning; Yahaya, Mohd Haizzan (Asian Social Work Journal, 2024)
International talent cultivation is an important part of the internationalization of higher education, and the cultivation of international talent is the trend of the times in line with the development of globalization. With the help of CiteSpace software, this paper combed and analyzed 618 pieces of related literature in the field of internationalization talent cultivation in the Web of Science database from 1996 to 2023. The results show that the research mainly focuses on China, and is mainly on international talent cultivation, teaching reform, and international talent management in various majors; the future research trend is mainly on international talent management, international talent education, and global competence. Among them, research on the training of international talents in social work is not sufficient. Currently, the research is mainly based on discursive suggestions, and more empirical research can be carried out in the future to summarize the advanced experiences at home and abroad, to provide a strong practical and theoretical basis for the cultivation of international talents.